Comparing internet and mobile phone usage:digital divides of usage, adoption, and dropouts - Ronald E. Rice James E. Katz (Telecommunications Policy 27 (2003) 597-623, 2003)
Results from a national representative telephone survey of Americans in 2000 show that Internet and mobile phone usage was very similar, and that several digital divides exist with respect to both Internet and mobile phone usage. The study identifies and analyzes three kinds of digital divides for both the Internet and mobile phones-users/nonuser, veteran/recent, and continuing/dropout-and similarities and differences among those digital divides based on demographic variables. The gap between Internet users and onusers is associated with income and age, but no longer with gender and race, once other variables are controlled. The gap between mobile phone users and nonusers is associated with income, work status, and marital status. The veteran/recent Internet gap is predicted by income, age, education, phone user, membership in community religious organizations, having children, and gender; for mobile phones, age, work status and marital status are predictors. The gap between continuing and dropout users is predicted by education for Internet usage and income for mobile phone usage. Finally, cross-categorization of Internet and mobile phone usage/nonusage is distinguished (significantly though weakly) primarily by income and education. Thus, there are several digital divides, each predicted by somewhat different variables; and while Internet and mobile phone usage levels in 2000 were about the same, their users overlap but do not constitute completely equivalent populations